2012
DOI: 10.4021/jocmr1061w
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Sitagliptin in the Treatment of Type 2 Diabetes Mellitus Patients

Abstract: BackgroundSitagliptin is a DPP-4 inhibitor that became available for use in Japan three years ago. This study was conducted to identify the pleiotropic effects of sitagliptin other than blood glucose lowering in Japanese type 2 diabetes mellitus patients.MethodsA retrospective, observational study of 940 type 2 diabetes mellitus patients was conducted. The primary outcome measures were HbA1c, blood pressure, and lipid profiles measured at 0, 4, and 12 weeks of sitagliptin therapy.ResultsAfter 12 weeks of sitag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 28 publications
5
35
5
Order By: Relevance
“…In the present study, sitagliptin did not cause any increase in the body mass index. Sitagliptin also decreases postprandial triglyceride level [27] and lowers blood pressure, blood lipid level [28] and alkaline phosphatase level [29]. Our present study also showed decreased systolic and diastolic blood pressures, decreased LDL-C level and decreased triglyceride levels, which is similar to results from previously published studies.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, sitagliptin did not cause any increase in the body mass index. Sitagliptin also decreases postprandial triglyceride level [27] and lowers blood pressure, blood lipid level [28] and alkaline phosphatase level [29]. Our present study also showed decreased systolic and diastolic blood pressures, decreased LDL-C level and decreased triglyceride levels, which is similar to results from previously published studies.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, we showed elevation of Cr and a correlation between elevation of Cr and reduction of the blood pressure with sitagliptin [3]. The new finding is a correlation between elevation of Cr and reduction of HbA1c.…”
Section: Discussionmentioning
confidence: 61%
“…Among the 1332 patients enrolled in this study, 826 patients have been taking sitagliptin for 24 months and HbA1c <7.0% (<53 mmol/mol) was achieved in 387 patients (46%). A significant increase in Cr, albeit within normal limits, have been reported in clinical studies in Japan [3,5]. On the other hand, elevation of Cr level was not reported in any of the previous studies carried out to evaluate the influence of sitagliptin on the renal function, including meta-analyses conducted in Western countries [6,7].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations